Family Experiences in Caring for Children with Stunting in Timor, East Nusa Tenggara, Indonesia: A Family-Centered Nursing Approach - Suhardin, Saverinus; Suwetty, Awaliyah Muslimah; Lede, Meldy Emry Hamdany; Riantiarno, Flavianus; Mella, Orni; Banamtuan, Desi Adiyanti (Utan Kayu Publishing, 2024)
Stunting is a critical global issue, particularly in developing countries such as Indonesia, where it significantly impacts children's health and development. This study aimed to explore the experiences of families in caring for children with stunting in Timor, Nusa Tenggara Timur, Indonesia. A qualitative phenomenological approach was employed, and nine families were selected through purposive sampling. Data were collected using in-depth interviews and observations over one month. Thematic analysis, supported by NVivo 14, was used to identify recurring themes. The study's findings are framed by the Family-Centered Nursing (FCN) theory, focusing on five key tasks: recognizing the problem, decision-making, caregiving capacity, modifying the environment, and utilizing healthcare services. Results indicated that while families recognized the issue of stunting, many attributed it to genetic factors. However, after guidance from healthcare workers, families engaged in available interventions, including attending Posyandu and participating in the government’s Supplementary Feeding Program. Families also expressed the need for educational reinforcement about stunting, particularly regarding its environmental and nutritional causes. Practical implications suggest the necessity of empowering families with skills to prepare complementary feeding using local resources and encouraging greater involvement of fathers in caregiving roles. Multisectoral approaches that involve healthcare, education, and social support are essential to effectively address stunting prevention. Abstrak: Stunting adalah masalah global yang krusial, terutama di negara berkembang seperti Indonesia, di mana hal ini memiliki dampak signifikan terhadap kesehatan dan perkembangan anak. Penelitian ini bertujuan untuk mengeksplorasi pengalaman keluarga dalam merawat anak dengan stunting di Timor, Nusa Tenggara Timur, Indonesia. Pendekatan fenomenologi kualitatif digunakan, dan sembilan keluarga dipilih melalui purposive sampling. Data dikumpulkan melalui wawancara mendalam dan observasi selama satu bulan. Analisis tematik, dengan dukungan NVivo 14, digunakan untuk mengidentifikasi tema yang berulang. Temuan penelitian ini dibingkai oleh teori Family-Centered Nursing (FCN), dengan fokus pada lima tugas utama: mengenali masalah, pengambilan keputusan, kapasitas perawatan, memodifikasi lingkungan, dan memanfaatkan layanan kesehatan. Hasil menunjukkan bahwa meskipun keluarga mengenali masalah stunting, banyak yang mengaitkannya dengan faktor genetik. Namun, setelah mendapatkan bimbingan dari tenaga kesehatan, keluarga terlibat dalam intervensi yang tersedia, termasuk menghadiri Posyandu dan berpartisipasi dalam Program Makanan Tambahan pemerintah. Keluarga juga menyatakan perlunya penguatan edukasi tentang stunting, terutama terkait dengan penyebab lingkungan dan gizi. Implikasi praktis menunjukkan perlunya memberdayakan keluarga dengan keterampilan untuk menyiapkan makanan pendamping ASI menggunakan sumber daya lokal dan mendorong keterlibatan yang lebih besar dari ayah dalam peran pengasuhan. Pendekatan multisektoral yang melibatkan kesehatan, pendidikan, dan dukungan sosial sangat penting untuk secara efektif menangani pencegahan stunting.